Pemanfaatan Koleksi Perpustakaan dalam Tesis dan Disertasi Mahasiswa Pascasarjana UIN Sunan Ampel: Studi Analisis Sitasi - Fistiyanti, Isna (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
AbstractBackground: The primary focus includes identifying the types of information sources used, measuring the extent of e-journal usage, and assessing the contribution of the university's subscribed electronic journal databases to students' final research.Objective: This study aims to analyze the utilization of electronic journals by postgraduate students at UIN Sunan Ampel in writing their theses and dissertations.Methods: The research employs a descriptive quantitative method, using numerical data to describe and analyze the situation. The subjects of the study are theses and dissertations uploaded to the UIN Sunan Ampel repository from 2019 to 2022. Data were collected using documentation techniques and analyzed through citation analysis.Results: Findings reveal that while students use various information sources, electronic journals contribute about 15% of the total references. However, the utilization of e-journals from the university’s subscribed database is relatively low, representing less than 1% of the total articles used.Conclusion: Graduate students at UIN Sunan Ampel utilize various information sources for thesis and dissertation writing, but the use of electronic journals from the university’s subscribed database is very low (less than 1%), highlighting the need for collection evaluation and the development of information literacy programs to enhance access and optimal use of digital resources.